Global dynamics of stochastic tidal equations. (December 2022) - Cardone, G.; Fouetio, A.; Lando, S. Talla; Woukeng, J.L.
Abstract: The current work deals with the global dynamics of 2 D stochastic tidal equations in a highly heterogeneous environment. With the help of the stochastic version of the sigma-convergence method in conjunction with the Prokhorov and Skorokhod compactness theorems, we prove that the dynamics at the macroscopic level is of the same type at the microscopic level, but this time with non oscillating parameters. We also prove a corrector-type result.